A Pilot Study to Establish the Leadership Development Needs of Community Pharmacist Leads in Lambeth, South East London - Mohammed Patel; Finlay Royle; Ricarda Micallef (Pharmacy, 2023)
Primary care networks (PCNs) are geographical networks consisting of 30,000 to 50,000 patients and groups of general practices working in a multidisciplinary team, including community pharmacists. Community pharmacy (CP) neighbourhood leads act as a conduit between pharmacy contractors and general practitioners (GPs) in these networks, sharing information and providing a voice for the community pharmacy locally. The Lambeth medicines team (NHS South East London Integrated Care Board) recognised the need to continue funding these leadership roles to address barriers to relationship-building between community pharmacies and general practices, the consistency of service delivery and effective communication. The aim of this study was to understand the current experience of CP neighbourhood leads to inform their further development. All eight CP neighbourhood leads individually completed a semi-structured interview over Microsoft Teams, which was then reviewed using content analysis. Ethical approval was received. Leads reported the use of common communication methods such as emails, text messaging applications and telephone calls to engage GPs and pharmacies in their neighbourhoods. Barriers to undertaking their roles included time constraints, delays in responses, high workloads and competing pressures. Other factors impacting their effectiveness and ability to undertake their roles included the scheduling of meetings outside of working hours, finding time during busy working days and organising locum cover on an ad hoc basis. The leads also reported they spent more time focussed on building relationships with their peers and less time focussed on general practice colleagues. Support for CP neighbourhood leads could include ensuring that funded time is protected; communication and technology training; and the provision of more structural support for communication with GPs. The findings of this study can be used to inform future work.